A Tetrabenzotriazaporphyrin Based Organic Thin Film Transistor: Comparison with a Device of the Phthalocyanine Analogue. (1st January 2015) - Chaure, Nandu B.; Cammidge, Andrew N.; Chambrier, Isabelle; Cook, Michael J.; Ray, Asim K.
Abstract : The characteristics of bottom-gate bottom-contact organic thin film field-effect transistors (OTFTs) with 70 nm thick films of solution processed non-peripherally octahexyl-substituted nickel tetrabenzo triazaporphyrin (6NiTBTAP) molecules as active layers on silicon substrates are experimentally studied and the results are compared with the similary configured transistors using the corresponding nickel phthalocyanine (6NiPc) compound. 6NiTBTAP transistors are found to exhibit improved performance over 6NiPc transistors in terms of greater saturation hole mobility, two orders of magnitude higher on/off ratio and lower threshold voltage. This enhanced performance of 6NiTBTAP OTFTs over 6NiPc devices is attributed to improved surface morphology and large grain size of the active 6NiTBTAP film.